Lithium ion battery and electronic equipment
By using positive electrode additives, sulfur-containing additives and 1,3-propanesulfonate lactone electrolyte in lithium-ion batteries, the shortcomings of lithium-ion batteries in high energy density, first-time Coulomb efficiency and low-temperature performance are solved, and higher battery performance and more stable cycle life are achieved.
Patent Information
- Application Number
- CN202411698477.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-25
AI Technical Summary
Existing lithium-ion batteries have shortcomings in high energy density, first-time Coulomb efficiency and low-temperature performance, especially in high and low-temperature environments.
By using an electrolyte containing a positive electrode additive and a sulfur-containing additive in a lithium-ion battery, combined with 1,3-propanesulfonic acid lactone, the matching of the positive electrode sheet and the electrolyte is optimized to improve the energy density, first-time Coulomb efficiency and low-temperature performance of the battery, while alleviating the side reactions of high temperatures.
It achieves high energy density, high first-time Coulomb efficiency and high and low temperature performance of lithium-ion batteries, especially in high and low temperature environments, and extends the cycle life of the battery.
Smart Images

Figure BDA0005153214060000021 
Figure BDA0005153214060000031 
Figure BDA0005153214060000081
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to lithium-ion batteries and electronic devices. Background Art
[0002] Lithium-ion batteries are widely used in consumer electronics, new energy vehicles, energy storage, etc. With the rapid development of the new energy vehicle industry, consumers have higher requirements for driving range and application scenarios, that is, batteries have higher energy density.
[0003] In the related technology, silicon materials have higher theoretical capacity than graphite materials, and are abundant in source and low in price, so they are widely used in lithium-ion batteries. However, silicon materials will expand and contract to a large extent during the process of metal ion insertion and extraction, resulting in degradation of electrochemical performance, which will be further aggravated in high temperature environments; in low temperature working environments, the viscosity of the electrolyte will increase, resulting in slower lithium ion migration rate and increased battery interface impedance, which will reduce the conductivity of the battery and ultimately lead to a decrease in the low-temperature cycle performance of the battery; in addition, during the first charging process of lithium-ion batteries, a solid electrolyte interface film (SEI) will form on the surface of the negative electrode, which will consume part of the active lithium in the positive electrode, resulting in a decrease in the first coulomb efficiency.
[0004] Therefore, it is urgent to develop a lithium-ion battery that has high energy density, high first coulombic efficiency and high and low temperature performance. Summary of the invention
[0005] In order to solve or partially solve the problems existing in the related art, the present application provides a lithium-ion battery and an electronic device, which can take into account high energy density, high first coulomb efficiency and high and low temperature performance.
[0006] In a first aspect, the present application provides a lithium ion battery, wherein the lithium ion battery comprises a positive electrode sheet and an electrolyte; the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, the positive electrode active material layer comprises a positive electrode additive; the electrolyte comprises a sulfur-containing additive and 1,3-propane sultone; the lithium ion battery satisfies the following relationship:
[0007] (X+Y) / (W*A)≥0.025
[0008] In the relationship, the mass percentage of the sulfur-containing additive in the electrolyte is X%; the mass percentage of 1,3-propane sultone in the electrolyte is Y%; the mass percentage of the positive electrode additive in the positive electrode active material layer is W%; the specific surface area of the positive electrode additive is A m 2 / g.
[0009] The lithium ion battery as described above, wherein the lithium ion battery satisfies the following relationship:
[0010] (X+Y) / (W*A)≥0.2.
[0011] The lithium ion battery as described above, wherein 0.01≤W≤10; and / or 0.1≤A≤10.
[0012] The lithium ion battery as described above, wherein A / W ≥ 0.1.
[0013] The lithium ion battery as described above, wherein 0.5≤X≤4; and / or 0.5≤Y≤4.
[0014] The lithium ion battery as described above, wherein X / Y≥0.25.
[0015] The lithium-ion battery as described above, wherein the positive electrode additives include Li2NiO2, Li6CoO4, Li5FeO4, Li2MnO3, Li6MnO4, LiMnFePO4, Li2C2O4, Li2O3Ti, LiTi2(PO4)3, LiLaTiO4, LiTaO3, Li 1.5 Al 0.5 Ge 1.5 At least one of (PO4)3.
[0016] The lithium-ion battery as described above, wherein the sulfur-containing additive comprises at least one of the compounds represented by Formula 1 to Formula 12:
[0017]
[0018]
[0019] The lithium-ion battery as described above, wherein the positive electrode active material layer further comprises a positive electrode active material, the chemical formula of the positive electrode active material is LiNi a Co b Mn (1-a-b) M c O2, wherein 0≤a≤0.9, a+b≤1, 0≤c<0.08, and M is at least one of Al, Mg, Zr and Ti.
[0020] A second aspect of the present application provides an electronic device, comprising the lithium-ion battery as described above.
[0021] The technical solution provided in the present application may include the following beneficial effects: when (X+Y) / (W*A)≥0.025, the positive electrode sheet of the lithium-ion battery is better matched with the electrolyte, the positive electrode additive can replenish lithium for the lithium-ion battery, and improve the initial coulombic efficiency of the lithium-ion battery. At the same time, there are fewer side reactions between the positive electrode additive and the positive electrode active material, and the low-temperature and high-temperature cycle performances can be better balanced. At the same time, the sulfur-containing additive and 1,3-propane sultone can synergistically form a film on the positive electrode additive and the positive electrode active material, further alleviating the side reactions between the positive electrode additive and the positive electrode active material, and improving the high-temperature cycle performance and high-temperature storage performance of the lithium-ion battery. The sulfonic acid group of 1,3-propane sultone can inhibit the generation of acidic substances such as HF, and the CEI film formed by the sulfur-containing additive on the positive electrode side has strong thermal stability, further improving the high-temperature cycle performance and high-temperature storage performance of the lithium-ion battery.
[0022] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present application. DETAILED DESCRIPTION
[0023] The terms used in this application are for the purpose of describing specific embodiments only and are not intended to limit this application. The singular forms of "a", "said" and "the" used in this application and the appended claims are also intended to include plural forms unless the context clearly indicates other meanings. It should also be understood that the term "and / or" used herein refers to and includes any or all possible combinations of one or more associated listed items.
[0024] It should be understood that although the terms "first", "second", "third", etc. may be used in this application to describe various information, this information should not be limited to these terms. These terms are only used to distinguish the same type of information from each other. For example, without departing from the scope of this application, the first information may also be referred to as the second information, and similarly, the second information may also be referred to as the first information. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of this application, the meaning of "multiple" is two or more, unless otherwise clearly and specifically defined.
[0025] In the related art, when lithium-ion batteries are working in a high-temperature environment, the internal working temperature of the lithium-ion batteries increases, and the silicon material will undergo a high degree of expansion and contraction during the process of metal ion embedding and extraction, which deteriorates the high-temperature cycle performance and high-temperature storage performance of the lithium-ion batteries; when lithium-ion batteries are working in a low-temperature environment, the viscosity of the electrolyte increases, resulting in a slower lithium ion migration rate and an increase in the interface impedance of the lithium-ion battery, which reduces the conductivity of the lithium-ion battery, and ultimately leads to a decrease in the low-temperature cycle performance of the lithium-ion battery; in addition, during the first charging process of the lithium-ion battery, the formation of the SEI film on the surface of the negative electrode will consume a portion of the active lithium in the positive electrode, resulting in a decrease in the first coulombic efficiency.
[0026] In view of the above problems, an embodiment of the present application provides a lithium ion battery, which includes a positive electrode sheet and an electrolyte; the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, and the positive electrode active material layer includes a positive electrode additive; the electrolyte includes a sulfur-containing additive and 1,3-propane sultone; the lithium ion battery satisfies the following relationship:
[0027] (X+Y) / (W*A)≥0.025
[0028] In the relationship, the mass percentage of sulfur-containing additive in the electrolyte is X%; the mass percentage of 1,3-propane sultone in the electrolyte is Y%; the mass percentage of positive electrode additive in the positive electrode active material layer is W%; the specific surface area of positive electrode additive is A m 2 / g.
[0029] It is understood that in this application, the specific surface area of the positive electrode additive refers to the total area of the positive electrode additive per unit mass, and the unit of the specific surface area of the positive electrode additive is m 2 / g, but the present application does not limit the unit of the specific surface area of the positive electrode additive. For example, the unit of the specific surface area of the positive electrode additive can also be cm 2 / g, etc. When the unit of specific surface area of positive electrode additive is m 2 / When the unit is other than g, the unit is converted to m 2 When the value of the formula obtained after adding 0.1% to 0.025 is greater than or equal to 0.025, it is also within the protection scope of the present application.
[0030] The lithium-ion battery of the present application includes a positive electrode sheet, which includes a positive electrode collector and a positive electrode active material layer arranged on at least one surface of the positive electrode collector, and the positive electrode active material layer includes a positive electrode active material, a positive electrode additive, a conductive agent and a binder, wherein the positive electrode collector is generally an aluminum foil. The present application does not limit the selection of positive electrode active materials, which can be selected according to actual needs. For example, lithium transition metal oxides and the like can be used as positive electrode active materials. The present application does not limit the selection of positive electrode additives, as long as the positive electrode additives can compensate for the active lithium consumed by the lithium-ion battery, which can be selected according to actual needs. For example, lithium supplement agents such as Li2NiO2 can be selected. The conductive agent and the binder in the positive electrode active material layer of the present application can be selected from conventional materials in the field.
[0031] The lithium-ion battery of the present application includes an electrolyte, wherein the electrolyte includes a sulfur-containing additive and 1,3-propane sultone, wherein the sulfur-containing additive refers to an additive containing sulfur element.
[0032] According to the above scheme provided in the present application, after the positive electrode sheet and the electrolyte are applied to a lithium-ion battery, the lithium-ion battery has excellent first coulombic efficiency, high-temperature cycle performance, high-temperature storage performance and low-temperature cycle performance. The applicant analyzed this principle and believed that the reason is that the first coulombic efficiency, high temperature cycle performance, high temperature storage performance and low temperature cycle performance of lithium-ion batteries are jointly determined by the positive electrode sheet and the electrolyte. The positive electrode additive can replenish lithium for the lithium-ion battery and improve the first coulombic efficiency of the lithium-ion battery. At the same time, since the conductivity of the positive electrode additive itself is poorer than that of the positive electrode active material, appropriately increasing the specific surface area of the positive electrode additive can increase the contact area between the electrolyte and the positive electrode additive, so that there are more transmission channels for lithium ions in the positive electrode additive, and the low temperature rate performance of the positive electrode additive is improved, thereby improving the low temperature cycle performance of the lithium-ion battery; however, during the cycle of the lithium-ion battery, the contact between the positive electrode additive and the positive electrode active material is poor, and the film forming potential and mechanism of the electrolyte at the positive electrode additive and the positive electrode active material are different, which will lead to the intensification of the electrolyte side reaction at the local contact interface between the positive electrode additive and the positive electrode active material. If the specific surface area of the positive electrode additive or the content of the positive electrode additive increases, the electrolyte contact surface will also increase, and the side reaction between the positive electrode additive and the positive electrode active material will intensify, which will lead to the accelerated deterioration of the high temperature performance of the lithium-ion battery. In order to improve the high temperature performance, sulfur-containing additives and 1,3-propane sultone are added to the electrolyte of the present application. This is because the sulfonic acid group of 1,3-propane sultone can inhibit the production of acidic substances such as HF to a certain extent during the high temperature storage of lithium-ion batteries, and the CEI film formed by the sulfur-containing additive on the positive electrode side has strong thermal stability. Therefore, 1,3-propane sultone and the sulfur-containing additive can effectively cooperate to form a film on the positive electrode additive and the positive electrode active material, alleviate the side reaction between the positive electrode additive and the positive electrode active material, thereby improving the high temperature cycle performance of lithium-ion batteries and high temperature storage gas production.
[0033] It can be understood that X is the mass percentage of the sulfur-containing additive in the electrolyte, and Y is the mass percentage of 1,3-propane sultone in the electrolyte, therefore, X+Y refers to the synergistic effect of the sulfur-containing additive and 1,3-propane sultone; W is the mass percentage of the positive electrode additive in the positive electrode active material layer, and A is the specific surface area of the positive electrode additive, therefore, W*A refers to the total specific surface area of the positive electrode additive in the positive electrode active material layer. Therefore, based on experience and experimental findings, the physical meaning of (X+Y) / (W*A) is actually the matching degree between the positive electrode and the electrolyte in the lithium-ion battery. When (X+Y) / (W*A)≥0.025, the positive electrode and the electrolyte of the lithium-ion battery are better matched, and the positive electrode additive can replenish lithium for the lithium-ion battery and improve the first coulomb efficiency of the lithium-ion battery. At the same time, the positive electrode additive can replenish lithium for the lithium-ion battery and improve the first coulomb efficiency of the lithium-ion battery. At the same time, the sulfur-containing additive and 1,3-propane sultone can synergistically form a film on the positive electrode additive and the positive electrode active material, effectively alleviate the side reaction between the positive electrode additive and the positive electrode active material, and improve the high temperature cycle performance and high temperature storage performance of the lithium-ion battery. In addition, the specific surface area of the positive electrode additive is reasonable, and the side reaction between the positive electrode additive and the positive electrode active material is less, which can better balance the low temperature and high temperature cycle performance. If (X+Y) / (W*A) is less than 0.025, the positive electrode sheet and the electrolyte are not properly matched, the stability of the formed CEI film is poor or there are more side reactions between the positive electrode additive and the positive electrode active material, thereby affecting the high temperature cycle performance, high temperature storage performance or low temperature cycle performance of the lithium-ion battery.
[0034] In a specific embodiment, (X+Y) / (W*A)≥0.2. When (X+Y) / (W*A)≥0.2, the positive electrode sheet and the electrolyte are more reasonably matched, the side reaction between the positive electrode additive and the positive electrode active material is less, the CEI film formed by the sulfur-containing additive and 1,3-propane sultone is more stable, the side reaction between the positive electrode additive and the positive electrode active material can be effectively alleviated, and the generation of acidic substances such as HF in the electrolyte can be better suppressed, thereby making the first coulombic efficiency, high temperature cycle performance, high temperature storage performance and low temperature cycle performance of the lithium-ion battery better.
[0035] In a specific embodiment, the mass percentage of the positive electrode active material layer is 100%, and the mass percentage of the positive electrode additive in the positive electrode active material layer is W%, 0.01≤W≤10, for example, W can be 0.01, 0.05, 0.1, 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10, etc. When the mass percentage of the positive electrode additive in the positive electrode active material layer is within the above range, the positive electrode additive can effectively supplement lithium to the lithium ion battery, and the side reaction between the positive electrode additive and the positive electrode active material is less, thereby improving the first coulombic efficiency, high temperature cycle performance and high temperature storage performance of the lithium ion battery.
[0036] In one embodiment, the specific surface area of the positive electrode additive is A m 2 / g, 0.1≤A≤10, for example, A can be 0.1, 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10, etc. When the specific surface area of the positive electrode additive is within the above range, the low temperature rate performance of the positive electrode additive can be improved, while avoiding aggravating the high temperature side reaction between the positive electrode additive and the positive electrode active material, so that the high temperature cycle performance, high temperature storage performance and low temperature cycle performance of the lithium ion battery can be taken into account.
[0037] In a specific embodiment, A / W≥0.1, A / W represents the relative ratio of the specific surface area of the positive electrode additive to the content of the positive electrode additive. If the specific surface area of the positive electrode additive remains unchanged, the higher the content of the positive electrode additive, the worse the cycle performance of the lithium ion battery; if the content of the positive electrode additive remains unchanged, the higher the specific surface area of the positive electrode additive, the better the cycle performance of the lithium ion battery. For example, A / W can be 0.1, 0.2, 0.5, 1, 2, 5 or 10. When the ratio of the specific surface area of the positive electrode additive to the mass percentage of the positive electrode additive is within the above range, the side reaction between the positive electrode additive and the positive electrode active material is less, and the positive electrode additive with a high specific surface area can improve the low temperature rate performance of the lithium ion battery, thereby achieving a better balance between the high temperature performance and the low temperature performance of the lithium ion battery.
[0038] In a specific embodiment, the mass fraction of the electrolyte is 100%, the mass percentage of the sulfur-containing additive in the electrolyte is X%, 0.5≤X≤4, for example, X can be 0.5, 1, 1.5, 2, 2.5, 3, 3.5 or 4. When the mass percentage of the sulfur-containing additive in the electrolyte is within the above range, the stability of the CEI film synergistically formed by the sulfur-containing additive and 1,3-propane sultone is better, and the impedance of the CEI film is lower, which is conducive to alleviating the side reaction of the positive electrode additive and the positive electrode active material, thereby effectively improving the high temperature cycle performance and high temperature storage performance of the lithium ion battery.
[0039] In a specific embodiment, the mass fraction of the electrolyte is 100%, the mass percentage of 1,3-propane sultone in the electrolyte is Y%, 0.5≤Y≤4, for example, Y can be 0.5, 1, 1.5, 2, 2.5, 3, 3.5 or 4. When the mass percentage of 1,3-propane sultone is within the above range, the stability of the CEI film formed by the sulfur-containing additive and 1,3-propane sultone is better, and the generation of acidic substances such as HF in the electrolyte can be effectively reduced. At the same time, it can avoid that the film formation impedance of 1,3-propane sultone on the positive electrode side is too large, resulting in excessive positive polarization, and avoid the deterioration of the high and low temperature cycle performance of the lithium ion battery.
[0040] In a specific embodiment, X / Y≥0.25, X / Y represents the ratio of the mass content of the sulfur-containing additive to 1,3-propane sultone, for example, X / Y can be 0.25, 0.3, 0.35, 0.4, 0.5, 1, 2, 5 or 8. Since the impedance of the CEI film formed by 1,3-propane sultone on the positive electrode surface is large, and the impedance of the CEI film formed by the sulfur-containing additive on the positive electrode surface is lower, if the mass content of the sulfur-containing additive is lower than the mass content of 1,3-propane sultone, the impedance of the CEI film on the positive electrode surface will be higher. When the mass percentage ratio of the sulfur-containing additive to 1,3-propane sultone is within the above range, the impedance of the CEI film formed on the positive electrode side is low and the stability is high, so that the side reaction of the positive electrode additive and the positive electrode active material is effectively alleviated, thereby further improving the high temperature cycle performance, high temperature storage performance and low temperature cycle performance of the lithium ion battery.
[0041] In a specific embodiment, the positive electrode additive includes Li2NiO2, Li6CoO4, Li5FeO4, Li2MnO3, Li6MnO4, LiMnFePO4, Li2C2O4, Li2O3Ti, LiTi2(PO4)3, LiLaTiO4, LiTaO3, Li 1.5 Al 0.5 Ge 1.5 At least one of (PO4)3. During the first charging process of a lithium-ion battery, a solid electrolyte interface film (SEI) will be formed on the surface of the negative electrode. This process will consume a portion of the active lithium in the positive electrode, resulting in a decrease in the first coulombic efficiency. When the positive electrode additive is selected from the above compounds, the positive electrode additive is a sacrificial lithium source, which can provide additional lithium ions to compensate for the active lithium consumed in the formation of the SEI film, thereby improving the first coulombic efficiency and energy density of the lithium-ion battery. At the same time, these positive electrode additives have fewer side reactions with the positive electrode active materials, which can better improve the high temperature cycle performance, high temperature storage performance and low temperature cycle performance of the lithium-ion battery.
[0042] In a specific embodiment, the sulfur-containing additive includes at least one of the compounds shown in Formula 1 to Formula 12:
[0043]
[0044] The sulfur-containing additive of the present application includes a five-membered cyclic carbonate group, a five-membered cyclic sulfate group, a six-membered cyclic carbonate group or a six-membered cyclic sulfate group, and the sulfur-containing additive includes at least one cyclic sulfate group, and the sulfate group or carbonate group in the sulfur-containing additive can participate in the formation of the interface film and improve the stability of the interface film. When the sulfur-containing additive is selected from the above compounds, the sulfur-containing additive and 1,3-propane sultone can better synergize to generate a more stable CEI film, thereby better alleviating the side reaction between the positive electrode additive and the positive electrode active material, and thus can further improve the high temperature cycle performance and high temperature storage performance of the lithium-ion battery.
[0045] In a specific embodiment, the electrolyte further includes an electrolyte salt, and the electrolyte salt includes at least one of lithium hexafluorophosphate, lithium difluorooxalatoborate, lithium bisoxalatoborate, lithium difluorobisoxalatophosphate, lithium tetrafluoroborate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, and lithium difluorophosphate; the molar concentration of the electrolyte salt in the electrolyte is 0.4 mol / L to 2.2 mol / L, for example, 0.4 mol / L, 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1 mol / L, 1.1 mol / L, 1.2 mol / L, 1.3 mol / L, 1.4 mol / L, 1.5 mol / L, 1.6 mol / L, 1.7 mol / L, 1.8 mol / L, 1.9 mol / L, 2 mol / L, 2.1 mol / L or 2.2 mol / L, etc. When the selection and molar concentration of the electrolyte salt are within the above range, the conductivity and stability of the electrolyte can be further improved, thereby further improving the first coulombic efficiency, high temperature cycle performance, high temperature storage performance and low temperature cycle performance of the lithium-ion battery.
[0046] In a specific embodiment, the electrolyte further includes an organic solvent, and the organic solvent includes at least one of ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, methyl propyl carbonate, diphenyl carbonate, methyl acetate, methyl propionate, methyl butyrate, methyl acetate, ethyl acetate, propyl acetate, ethyl butyrate, propyl propionate, γ-butyrolactone, 1,3-dioxolane, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether and tetraethylene glycol dimethyl ether. When the organic solvent of the electrolyte is selected from the above organic solvent, the viscosity of the electrolyte is lower and the ion conductivity is higher, which is conducive to improving the migration rate of lithium ions, thereby improving the high and low temperature cycle performance of the lithium ion battery, and the above organic solvent can improve the stability of the electrolyte, avoid the decomposition reaction of the electrolyte, thereby further improving the high temperature storage performance of the lithium ion battery.
[0047] In a specific embodiment, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer coated on the positive electrode current collector, the positive electrode active material layer includes a positive electrode active material, and the chemical formula of the positive electrode active material is LiNi a Co b Mn (1-a-b) M c O2, wherein 0≤a≤0.9, a+b≤1, 0≤c<0.08, and M is at least one of Al, Mg, Zr and Ti. When the positive electrode active material is selected from the above compounds, the positive electrode active material can give full play to its performance and improve the electrochemical performance of the lithium ion battery. At the same time, the side reaction between the positive electrode active material and the positive electrode additive is low, which can improve the high temperature cycle performance, high temperature storage performance and low temperature cycle performance of the lithium ion battery.
[0048] In the embodiments of the present application, there is no particular restriction on the type of the positive electrode current collector, which can be any known material suitable for use as a positive electrode current collector. In one embodiment, the positive electrode current collector includes metal materials such as aluminum, stainless steel, nickel plating, titanium, tantalum, and carbon materials such as carbon cloth and carbon paper. Preferably, the positive electrode current collector is a metal material.
[0049] In a specific embodiment, the positive electrode active material layer further includes a conductive agent and a binder. The conductive agent includes at least one of carbon materials such as natural graphite, artificial graphite, acetylene black, needle coke, carbon nanotubes, graphene, etc. The binder includes at least one of polyethylene, polypropylene, polyethylene terephthalate, polymethyl methacrylate, polyimide, aromatic polyamide, cellulose, and nitrocellulose.
[0050] In a specific embodiment, the lithium-ion battery also includes a negative electrode sheet, the negative electrode sheet includes a negative electrode collector and a negative electrode active material layer arranged on the surface of the negative electrode collector, the negative electrode active material layer includes a negative electrode active material, a conductive agent and a binder, wherein the embodiment of the present application has no special restrictions on the negative electrode collector, as long as the purpose of the present application can be achieved, for example, it can be copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, foam nickel, foam copper or a composite current collector, etc., and the negative electrode active material is selected from at least one of graphite, hard carbon, soft carbon, mesophase carbon microspheres, silicon-carbon particles and lithium-containing metal composite oxide materials.
[0051] The conductive agent and the binder in the negative electrode active material layer of the embodiment of the present application can be selected from conventional materials in the art.
[0052] In a specific embodiment, the lithium-ion battery also includes a diaphragm. The embodiment of the present application has no particular restrictions on the material and shape of the diaphragm, as long as it does not significantly damage the effect of the present application. It can include porous sheet-like or non-woven fabric-like materials with excellent liquid retention, etc. The materials of the resin or glass fiber diaphragm include but are not limited to polyolefins, aromatic polyamides, polytetrafluoroethylene, polyether sulfone, etc., and can be specifically set according to needs.
[0053] In a specific embodiment, the lithium-ion battery may include an outer packaging, which can be used to encapsulate the electrode assembly and the electrolyte.
[0054] In a specific embodiment, the outer packaging of the lithium ion battery can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, and as the plastic, polypropylene, polybutylene terephthalate, and polybutylene succinate can be listed.
[0055] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square, or any other shape.
[0056] The embodiment of the present application also provides an electronic device, comprising the above-mentioned lithium-ion battery. The electronic device has the same advantages as the above-mentioned lithium-ion battery, which will not be described in detail.
[0057] The electronic devices of the embodiments of the present application may be conventional electronic devices in the art. By way of example, the electronic devices may include mobile devices (such as mobile phones, laptop computers, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., without particular limitation.
[0058] Hereinafter, the present application will be further described in detail through specific embodiments.
[0059] Example 1
[0060] 1. Preparation of positive electrode
[0061] The positive electrode active material LiCoO2, the positive electrode additive Li2NiO2, the conductive agent acetylene black (SuperP) and the polyvinylidene fluoride (PVDF) binder are mixed uniformly in a mass ratio of 96.5:0.5:1.5:1.5, and evenly dispersed with 1-methyl-2-pyrrolidone (NMP) to form a uniform black slurry. The mixed slurry is coated on both sides of the aluminum foil current collector, and then baked, rolled, and cut into pieces to obtain a positive electrode sheet. Among them, the coating surface density of the positive electrode active material layer and the mass percentage of the positive electrode additive in the positive electrode active material layer are shown in Table 1.
[0062] 2. Preparation of negative electrode sheet
[0063] The negative electrode active materials graphite and silicon carbon particles (mass ratio of 9:1), conductive agent acetylene black (Super P), thickener CMC and binder SBR are mixed evenly in a mass ratio of 94:2:1.2:2.8, and evenly dispersed in deionized water to form a uniform black slurry. The mixed slurry is coated on both sides of the aluminum foil current collector, and then baked, rolled and cut into pieces to obtain the negative electrode sheet.
[0064] 3. Preparation of electrolyte
[0065] a. Ethylene carbonate (EC), propylene carbonate (PC), propyl propionate (PP) and diethyl carbonate (DEC) are mixed and stirred in a mass ratio of 10:20:40:30 to form a mixed solvent, and water is removed by molecular sieves for standby use. 1M lithium hexafluorophosphate (LiPF6) is added and mixed evenly;
[0066] b. Add a sulfur-containing additive and an additive Y (the types and amounts of the additives are shown in Table 1) to the colorless transparent liquid obtained in step a to obtain the electrolytes of the embodiments and comparative examples.
[0067] 4. Production of lithium-ion batteries
[0068] The positive electrode sheet, separator and negative electrode sheet are stacked in order, so that the separator is in the middle of the positive and negative electrodes to play an isolating role, and then wound to the bare battery cell. The bare battery cell is placed in an outer packaging bag and dried at high temperature until the water content of the electrode sheet is less than 100ppm, and then the prepared electrolyte is injected. After vacuum packaging, standing, formation, shaping and other processes, the preparation of the lithium-ion battery is completed.
[0069] The preparation methods of the lithium ion batteries provided in Examples 2 to 48 and Comparative Examples 1 to 27 are substantially the same as that in Example 1, and the specific parameters are shown in Table 1.
[0070] Table 1
[0071]
[0072]
[0073]
[0074]
[0075] Test example
[0076] Lithium-ion battery performance test:
[0077] 1. First Coulomb efficiency test:
[0078] After the lithium-ion battery is filled, it is left at room temperature for 48 hours, and the lithium-ion battery is charged to 4.53V at a rate of 0.3C, with a cut-off current of 0.05C, and the charging capacity C0 is recorded. It is left for 10 minutes; then it is discharged to 3.0V at a rate of 0.2C, and the discharge capacity C1 is recorded. The first efficiency = C1 / C0*100%, and the average value is recorded in Table 2.
[0079] 2. 45℃ cycle test:
[0080] The test method is: in a 45±2℃ constant temperature box, charge the lithium-ion battery to 4.53V at 1C constant current and constant voltage, cut off the current at 0.05C, and then discharge it to 3V at 1C. Perform multiple charge and discharge cycles under the above conditions, and calculate the capacity retention rate of the battery after 600 cycles, with 5 batteries in each group.
[0081] Capacity retention rate (%) = discharge capacity corresponding to the number of cycles (mAh) / discharge capacity of the third cycle (mAh) * 100%
[0082] The average value of the capacity retention rate of each group of 5 batteries after different cycles is recorded in Table 2.
[0083] 3. 0℃ cycle test:
[0084] The test method is: in a 0±2℃ constant temperature box, charge the lithium-ion battery to 4.53V at 1C constant current and constant voltage, cut off the current at 0.05C, and then discharge it to 3V at 1C. Perform multiple charge and discharge cycles under the above conditions, and calculate the capacity retention rate of the battery after 600 cycles, with 5 batteries in each group.
[0085] Capacity retention rate (%) = discharge capacity corresponding to the number of cycles (mAh) / discharge capacity of the third cycle (mAh) * 100%
[0086] The average value of the capacity retention rate of each group of 5 batteries after different cycles is recorded in Table 2.
[0087] 4. 60℃ storage performance test:
[0088] The test method is: charge the lithium-ion battery to 4.53V at 1C constant current and constant voltage in a 25±2℃ constant temperature box, with a cut-off current of 0.05C, and test the thickness of the lithium-ion battery (this is the thickness before storage). Place the fully charged cell / battery at (60±2)℃ for 35 days in an open circuit, and then place it at room temperature for 2 hours after 35 days of storage, and test the thickness after storage, and calculate the thickness expansion rate of the lithium-ion battery:
[0089] Thickness expansion ratio = [(thickness after storage - thickness before storage) / thickness before storage] × 100%. The results are recorded in Table 2.
[0090] Table 2
[0091]
[0092]
[0093]
[0094] According to the comparison between Examples 1 to 48 and Comparative Example 27, when the total amount of sulfur-containing additives and PS (1,3-propane sultone) is too low relative to the positive electrode additive and the specific surface area content, it is not enough to improve the side reactions at the interface of the positive electrode additive. Therefore, it is necessary to meet the following conditions: when (X+Y) / (W*A)≥0.025, the comprehensive performance of the lithium-ion battery is relatively good. According to the comparison between Examples 1 to 44 and Examples 45 to 48, when (X+Y) / (W*A)≥0.2, the comprehensive performance of the lithium-ion battery is better.
[0095] According to the comparison between Example 4, Example 12 and Comparative Examples 1 to 6, when the positive electrode additive, the sulfur-containing additive and PS act synergistically in the lithium-ion battery, the lithium-ion battery can take into account high first coulombic efficiency, high and low temperature cycle performance and high temperature storage performance.
[0096] According to the comparison of Examples 11 to 16, as the content of the positive electrode additive increases, the first coulombic efficiency of the lithium-ion battery increases, and the high and low temperature cycle performance and high temperature storage performance of the lithium-ion battery deteriorate. According to the data of Examples 17 to 22, as the specific surface area of the positive electrode additive increases, the low temperature cycle performance of the lithium-ion battery is improved, the first efficiency has no significant change, and the high temperature cycle deteriorates. When the positive electrode active material is highly delithiated, the positive electrode additive can be used as a lithium source to supplement lithium, thereby improving the first efficiency and capacity of the lithium-ion battery. However, during the cycle of the electrochemical device, the contact between the positive electrode additive and the positive electrode active material is poor, and the electrolyte has differences in the film forming potential and mechanism between the positive electrode additive and the positive electrode active material, which will lead to the intensification of the electrolyte side reaction at the local contact interface of the two materials. When the specific surface area of the positive electrode additive increases, the electrolyte contact surface will also increase. Therefore, when the proportion of the positive electrode additive in the positive electrode active material layer increases and the specific surface area increases, the side reaction between the positive electrode additive and the positive electrode active material will intensify. The conductivity of the positive electrode additive itself is worse than that of the positive electrode active material. Therefore, increasing the specific surface area of the positive electrode material can improve the low-temperature rate performance of the positive electrode additive, but too high a specific surface area will aggravate the high-temperature side reaction, so the specific surface area of the positive electrode additive and the content of the positive electrode additive need to be within a certain range to better balance the low-temperature and high-temperature cycle performance. According to the comparison of Examples 11 to 22 and Comparative Examples 21 to 22 and Comparative Examples 25 to 26, when 0.01≤W≤10, 0.1≤A≤10, and A / W≥0.1, the comprehensive performance of the lithium-ion battery is relatively good. According to the comparison of Example 4 and Examples 34 to 44, when the above-mentioned compounds are selected as the positive electrode additives, the lithium-ion battery can take into account the first coulomb efficiency, high and low temperature cycle performance, and high temperature storage performance.
[0097] Sulfur-containing additives and additive 1,3-propane sultone can effectively cooperate to form a film on the positive electrode additive and the positive electrode active material, alleviate the side reaction between the positive electrode material and the positive electrode active material, and thus improve the high temperature cycle performance and high temperature storage gas production of lithium-ion batteries. When the total amount of sulfur-containing additives and additive 1,3-propane sultone is within a certain range relative to the content and specific surface area of the positive electrode additive, the low temperature and high temperature performance can be better balanced. During the high temperature storage of lithium-ion batteries, the sulfonic acid group of 1,3-propane sultone can inhibit the generation of HF to a certain extent, thereby improving storage gas production; on the other hand, the CEI film formed by the sulfur-containing additive on the positive electrode side has strong thermal stability, so 1,3-propane sultone and sulfur-containing additives can cooperate to effectively improve the high temperature storage performance of lithium-ion batteries. However, 1,3-propane sultone has a large film-forming impedance on the positive electrode side, and when the content is too high, it is easy to cause excessive polarization of the positive electrode, deteriorating the high and low temperature cycle performance; on the other hand, the sulfur-containing additive forms a low impedance CEI film on the positive electrode side. When the total amount of the two is the same, when the content of 1,3-propane sultone decreases and the amount of sulfur-containing additive increases, the high temperature cycle is improved. According to the comparison of Examples 1 to 4, it can be seen that as the content of sulfur-containing additives increases, the cycle performance and storage performance of lithium-ion batteries are improved. According to the comparison of Examples 7 to 10, it can be seen that as the content of 1,3-propane sultone increases, the cycle performance of lithium-ion batteries deteriorates, but the high temperature storage performance is improved. According to the comparison of Example 12 and Comparative Examples 2, 7 to 9, 12, 14 to 16, 19 to 20 and the comparison of Example 4 and Comparative Examples 3, 10 to 11, 13, 17 to 18, it can be seen that only when the sulfur-containing additive and PS are used together can a good synergistic effect be exerted, and the additive content should not be too high, which will lead to an increase in electrolyte viscosity and an increase in impedance. According to Examples 5 to 6, when the total amount of additives remains unchanged, the sulfur-containing additive is increased to reduce PS, the cycle performance of the lithium-ion battery is improved, and the storage performance is slightly deteriorated. According to Examples 4, 7 to 10, and Comparative Examples 23 to 24, the relative PS content of the sulfur-containing additive needs to be guaranteed to be within a certain range in order to effectively improve the deterioration of PS on the positive electrode impedance. The following relationship is satisfied: 0.5≤X≤4, 0.5≤Y≤4, X / Y≥0.25 when the comprehensive performance of the lithium-ion battery is relatively good. According to the comparison of Example 5 and Examples 24 to 34, when the sulfur-containing additive is selected from the compounds shown in Formula 1 to Formula 12, the sulfur-containing additive and PS can act synergistically, thereby improving the comprehensive performance of the lithium-ion battery.
[0098] The embodiments of the present application have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The selection of terms used herein is intended to best explain the principles of the embodiments, practical applications, or improvements to the technology in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.
Claims
1. A lithium ion battery, characterized in that: The battery comprises a positive electrode sheet and an electrolyte; the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, the positive electrode active material layer comprises a positive electrode additive; the electrolyte comprises a sulfur-containing additive and 1,3-propane sultone; the lithium ion battery satisfies the following relationship: (X+Y) / (W*A)≥0.025 In the relationship, the mass percentage of the sulfur-containing additive in the electrolyte is X%; the mass percentage of 1,3-propane sultone in the electrolyte is Y%; the mass percentage of the positive electrode additive in the positive electrode active material layer is W%; the specific surface area of the positive electrode additive is Am 2 / g.
2. The lithium-ion battery according to claim 1, characterized in that The lithium-ion battery satisfies the following relationship: (X+Y) / (W*A)≥0.
2.
3. The lithium-ion battery according to claim 1, characterized in that 0.01≤W≤10; and / or, 0.1≤A≤10.
4. The lithium ion battery according to claim 1 or 3, characterized in that: A / W≥0.
1.
5. The lithium-ion battery according to claim 1, characterized in that: 0.5≤X≤4; and / or, 0.5≤Y≤4.
6. The lithium ion battery according to claim 1 or 5, characterized in that: X / Y ≥ 0.
25.
7. The lithium-ion battery according to claim 1, characterized in that: The positive electrode additives include Li2NiO2, Li6CoO4, Li5FeO4, Li2MnO3, Li6MnO4, LiMnFePO4, Li2C2O4, Li2O3Ti, LiTi2(PO4)3, LiLaTiO4, LiTaO3, Li 1.5 Al 0.5 Ge 1.5 At least one of (PO4)3.
8. The lithium-ion battery according to claim 1, characterized in that The sulfur-containing additive includes at least one of the compounds shown in Formula 1 to Formula 12:
9. The lithium-ion battery according to claim 1, characterized in that: The positive electrode active material layer also includes a positive electrode active material, the chemical formula of which is LiNi a Co b Mn (1-a-b) M c O2, wherein 0≤a≤0.9, a+b≤1, 0≤c<0.08, and M is at least one of Al, Mg, Zr and Ti.
10. An electronic device, characterized in that: A lithium ion battery comprising any one of claims 1 to 9.
Citation Information
Patent Citations
Lithium ion battery
CN114725392A
Positive pole piece and battery
CN116259712A
Lithium ion battery and electric device comprising same
CN116632320A
Lithium ion battery
CN118867129A
Highly sensitive and selective gas sensor and preparing method thereof
KR1020250043843A
Cited By
Battery cell, battery apparatus and electrical apparatus
WO2026026099A1